Analysis of the Meaning of the Word Bahr in the Qur’an: Toshihiko Izutsu's Semantic Perspective - Mustaqimah; Kharis Nugroho; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to examine the concept of the word